Líderes para a sustentabilidade e os objetivos de desenvolvimento sustentável: uma articulação entre a teoria de papéis e a psicologia ambiental - Souza, Débora de Mello e (2018)
This study investigated the narrative of sustainability leaders, working in organizational contexts, and identified the interaction and variation of their choices in assessing sustainability issues, at first, in the role of leader and then in other roles of their lives. We used the qualitative approach, based on concepts of environmental psychology to analyze the descriptive contents narrated by the participants, articulating to these concepts the Role Theory, proposed by Jacob Levy Moreno. Twelve leaders, high level occupants (presidents, vice presidents and directors) were interviewed in different economic sectors in the Southeastern and Southern regions of Brazil. The inclusion and exclusion criteria took into account participants who are active in sustainability initiatives in their organizations. The general analysis of the data enabled us to construct a collective case study, as recommended by Stake (1995), based on the in- depth analysis of the data of four participants: two women and two men. The research method included firstly a semistructured interview, based on sociopsychodramatic perspective, in which the participants reported the development of their role as leaders for sustainability, as well as the proposal to reflect on a set of numbered cards and the application of an instrument, called “Approach Map” in association with a adapted scale called EFA-A, both instruments specifically developed for this study, based on sustainable development goals (ONU, 2015). The procedure establishment allowed an analysis of variations in answers for each one of the participants when they took on different roles. Conclusions indicated an important relationship among roles, behavior and decision-making processes regarding sustainability, reinforcing viability and contribution of the designed method in new interventions focused on actions for sustainability